Плазменная нанопорошковая металлургия - Цветков, Ю.В.; Самохин, А.В. (Автоматическая сварка, 2008)
Generalized are the results of many years of research aimed at development of physico-chemical fundamentals and optimum design-technological realization of the processes of plasma nanopowder metallurgy, ensuring the production of a wide range of powders of the nanosized elements and compounds to produce on their basis nanostructured functional and structural materials with special properties. The main directions are determined in the path of application of the produced nanopowders and commercialization of the developed processes of plasma nanopowder metallurgy.